Max the missing puppy - Webb,Holly; Williams, Sophy (London Stripes Publishing, 2008)
"Molly is thrilled when her family adopts a beautiful Old English sheepdog puppy. She names the puppy Max, and soon, the two are inseparable. Max misses Molly when she's at school, and he longs for her to come home and play. One day, Max gets out of the house through an open window and sets off to find Molly. But the world is a scary place for a puppy, and before long, Max is lost and in danger. How will he ever find Molly and get back home safely?"